'A project to establish joy': Jean Giono, happiness and the framing of environmentalism. Issue 2 (4th May 2017) - Mortensen, Peter
ABSTRACT: This essay combines ecocritical and eudaimonic (happiness-oriented) reading strategies to consider the French writer Jean Giono's fiction from the 1930s. Making (un)happiness its central problem, Giono's therapeutic novel explores how disconnection from nature causes misery and hypothesises ways in which renewed contact with non-human nature can in turn enhance human well-being. Giono's eco-centred understanding of happiness, I argue, points forward to present-day debates and arguments about the nature of happiness. In addition, it provides inspiration for an alternative and potentially more effective strategy by which the necessity and desirability of pro-nature concern and behaviour can be framed.